Survey of The Influence of Self Efficacy and Self Resilience to Biology Education Students to Overcoming Learning Loss - Surtika, Surtika; Firdaus, L.N, Firdaus, L.N; Syafii, Wan (FKIP-Universitas Riau, 2024)
Distance learning during the COVID-19 pandemic has encountered various challenges. Some of those include uneven internet connectivity, inadequate facilities, and an unsupportive learning environment. Those challenges gradually decreased students' learning motivation and result in learning loss. Their motivation could be influenced by several factors, including self-efficacy and self-resilience. This research aims to determine the extent to which self-efficacy and self-resilience influence learning loss compared to other factors. To achieve this goal, a quantitative approach and survey methods were applied in this cross- sectional research by using biology education students at Riau University as subjects. Its findings indicate a significant simultaneous influence of self-efficacy and self-resilience on students' learning loss. Facility disparities, unstable internet conditions, short learning time, and low interaction between instructors and students are among the factors causing learning loss in students during the distance learning. The conclusions that can be drawn from this research are learning loss is influenced by various factors, including self-efficacy and resilience. This study highlights that the low levels of self-efficacy and resilience observed in students are a result of the declining motivation for learning during remote education.